Christian Ethics toward Artificial Intelligence and Its Impacts on Humanity - Ester Agustini Tandana (Evangelikal: Jurnal Teologi Injili dan Pembinaan Warga Jemaat, 2023)
Innovation in Artificial Intelligence raise a plethora of moral concerns, the majority of which are being thoughtfully explored by organizations ranging from small societal groups to large organizations and governments. Nevertheless, they raise ethical concerns that are not being adequately addressed. This research offers a comprehensive overview of the main ethical issues linked to the impact of Artificial Intelligence on human society from the perspective of Christian ethics. Christian ethics stresses human individuals’ intrinsic dignity as being made in the image of God (Imago Dei). It emphasizes the relevance of human dignity, well-being, and autonomy in the development and implementation of Artificial Intelligence. Having established a number of potential qualities of human identity, we then turn to the Scriptures in order to discover some biblical notions that may be helpful in addressing Artificial Intelligence and the meaning of being human, organized around the themes of creation, fall, and redemption. The report concludes with a call for accountability and humility.